Mass-difference measurements on heavy nuclides with an eV/c2 accuracy in the PENTATRAP spectrometer - Rischka, Alexander; Cakir, Halil; Door, Menno; Filianin, Pavel; Harman, Zoltán; Huang, Wenjia; Indelicato, P.; Keitel, Christoph H.; König, Charlotte; Kromer, Kathrin; Müller, Marius; Novikov, Y. N.; et al. (Physical review letters, 2020)
First ever measurements of the ratios of free cyclotron frequencies of heavy, highly charged ions with Z>50 with relative uncertainties close to 10−11 are presented. Such accurate measurements have become realistic due to the construction of the novel cryogenic multi-Penning-trap mass spectrometer PENTATRAP. Based on the measured frequency ratios, the mass differences of five pairs of stable xenon isotopes, ranging from 126Xe to 134Xe, have been determined. Moreover, the first direct measurement of an electron binding energy in a heavy highly charged ion, namely of the 37th atomic electron in xenon, with an uncertainty of a few eV is demonstrated. The obtained value agrees with the calculated one using two independent, different implementations of the multiconfiguration Dirac-Hartree-Fock method. PENTATRAP opens the door to future measurements of electron binding energies in highly charged heavy ions for more stringent tests of bound-state quantum electrodynamics in strong electromagnetic fields and for an investigation of the manifestation of light dark matter in isotopic chains of certain chemical elements.
Die 2 in eV/c2 im Titel ist hochgestellt
Gesehen am 14.04.2020